An update about neck rejuvenation and complications - Viterbo, Fausto [UNESP]; Secanho, Murilo Sgarbi [UNESP] (OAE Publishing, 2021)
The submental-cervical angle is an important anatomical landmark in neck beauty. Considered attractive and a sign of youthful when between 105° and 120°, greater values are considered a “heavy” neck or double chin and are related to the aging process and/or weight gain. The submandibular gland can also contribute to the alteration of the submental-cervical angle, increasing the area’s bulging. Neck-lifting techniques have the potential to produce important changes in the lateral view of the face, making it look more youthful, and that is more noticeable in the frontal aspect. This review focuses on the treatment of the neck, including all modifications that occur during the aging process, and postoperative procedures used to decrease the risk of complications.
Keywords: blunt dissectors; Facial rejuvenation; hemostatic net; neck lift; neck lifting; neck rejuvenation